Lung parenchymal calcifications in a child with cystic fibrosis. Issue 5 (31st March 2022) - Lynch, Heidi; Qian, Frank; Wong, Matthew D.; Thomas, Rahul J.; Kapur, Nitin
Abstract: We describe a 6‐year‐old girl with homozygous p.Phe508del cystic fibrosis with severe multi‐lobar bronchiectasis and obstructive lung disease who was found to have prominent parenchymal calcifications in the right middle lobe on a computed tomography scan of the chest. Histopathology from the calcified area of lung biopsy showed fibrous tissue with chronic inflammation with CD3+ T‐lymphocytes and macrophages with no granulomas. Dystrophic calcification was seen within this necrotic debris. Abstract : This study reports the first case of extensive parenchymal lung calcification in a child with cystic fibrosis. The aetiology of lung calcification in this case is not attributable to metastatic lung calcification or tubercular mycobacterial infection.